Afropolitanism and the (Re)definition of African Identity in Chimamanda Ngozy Adichie’sAmericanah - BENBEDRA, FATIMA ZOHRA (My University, 2018)
This research investigates how the members of new African generation who call themselves Afropolitan challenge racism and stereotypes in America. The study uses ChimamandaNgozyAdichie’s novel Americanahas a case study. The choice of this novel is made on purpose because Adichie, is one representative of the Afropolitan movement in addition of being a feminist , this young Nigerian moves across nations questioning her identity not only as an African living in America but also as a woman. She is multilingual and a culturally hybrid i.e she has a mixed culture due to her constant encounters with the rest of the world. Moreover, through her novel, Adichie exposes characters who own more than one characteristic of the Afropolitan identity mentioned by Selasie, Mbembe and Gikandi. The research concludes that the Afropolitan individual challenges racism and stereotypes by first questioning the nation he is living as victim of the injustice inflicted on his minority group, then, asserting his national identity or the love of the country of origin. Finally, he expresses his attachment to his African culture as a brand of self esteem and dignity.
Keywords: Afropolitan movement; Chalenge and struggle; Chimamanda Ngozy Adichie’s, Americanahas novel; Critic and analyse